Encapsulation of Bioactive Compounds (Handbook of Encapsulation and Controlled Release, 2016)
The scientic and industrial interest for functional foods, where bioactive compounds are incorporated, has been signicantly reinforced in recent years by the increasing demand from consumers for health promotion and disease prevention through diet and nutrition.